2009
DOI: 10.1021/es802679b
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Volatile Organic Compounds by Single-Stage and Two-Stage Plasma Catalysis Systems: A Review of the Performance Enhancement Mechanisms, Current Status, and Suitable Applications

Abstract: This paper provides a comprehensive review regarding the application of plasma catalysis, the integration of nonthermal plasma and catalysis, on VOC removal. This novel technique combinesthe advantages of fast ignition/response from nonthermal plasma and high selectivity from catalysis. It has been successfully demonstrated that plasma catalysis could serve as an effective solution to the major bottlenecks encountered by nonthermal plasma, i.e., the reduction of energy consumption and unwanted/hazardous byprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
157
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(162 citation statements)
references
References 73 publications
1
157
0
1
Order By: Relevance
“…Plasma catalysis is gaining increasing interest for various environmental applications, such as gaseous pollutant removal, the splitting of CO 2 , hydrogen generation and O 3 production [1][2][3][4][5][6][7][8][9]. Plasma catalysis can be regarded as the combination of a plasma with a catalyst, and often results in improved performance, in terms of selectivity and energy efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma catalysis is gaining increasing interest for various environmental applications, such as gaseous pollutant removal, the splitting of CO 2 , hydrogen generation and O 3 production [1][2][3][4][5][6][7][8][9]. Plasma catalysis can be regarded as the combination of a plasma with a catalyst, and often results in improved performance, in terms of selectivity and energy efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the existence of Ce 3+ in CeO 2 implies the formation of an oxygen vacancy, and subsequently increasing catalytic activity [12]. Moreover, the generation of Cu + together with Ce 3+ is indicative of the redox equilibrium (Ce 3+ + Cu 2+ ↔ Ce 4+ + Cu + ), which is claimed to be the enhancement of reduced copper species [13].…”
Section: Characterizationsmentioning
confidence: 99%
“…Plasma catalysis technique also has the advantages of high selectivity from catalysis and the fast response from plasma technique. Reports on plasma catalysis mainly focus on environmental clean-up removing volatile organic compounds (VOCs) from gaseous pollutants [10] and hydrocarbon reforming for hydrogen production [11]. There are two ways of combination: the catalyst placed in the discharge zone (in-plasma catalysis, IPC) or the catalyst placed after the discharge zone (post-plasma catalysis, PPC).…”
Section: Figurementioning
confidence: 99%